Innovation Policy and Governance in High-Tech Industries The Complexity of Coordination - Bauer, Johannes; Lang, Achim; Schneider, Volker; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
The book examines the conditions for successful high-technology policy from theoretical and empirical perspectives. It enhances the predominant national systems of innovation approach to innovation policy with concepts based on new developments in the govern-ance of complex systems and processes. The conceptual framework of complex networks and systems is used to examine national policy approaches in countries that have created environments conducive to high-technology industries as well as individual high-technology sectors, such as biotechnology, alternative energy, and aerospace. Theoretical and empirical contributions are synthesised into lessons for high-tech policy and further research.
Introduction -- Part I: Theories and Concepts of Innovation Policy -- Part II: National Systems of Innovation and High-tech Policies -- Part III: Sectoral Perspectives on Innovation Policy -- Part IV: Conclusions.
Keywords: Economics; Economics/Management Science; R & D/Technology Policy; Innovation/Technology Management; Political Science, general